Resource recovery from wastewater treatment: challenges, opportunities and guidance for planning and implementation - Chrispim, Mariana Cardoso (2021)
Considering the current resources scarcity, Wastewater Treatment Plants (WWTP) should be adapted to become more sustainable. For example, it is possible to recover resources present in municipal wastewater. However, regional studies about integration of resource recovery processes at different scales or about the main barriers to implementation in developing countries are missing in the literature. Also, there is a need for planning methodologies to identify the most sustainable solution in each context. Understanding the current situation is an essential step to support planning and accelerate resource recovery implementation. To address these issues this thesis aims to guide planning, technology and policy development towards resource recovery from municipal WWTP in large cities of developing countries. This thesis presents a comprehensive knowledge base for wastewater treatment plant managers and decision-makers leading to a better understanding of resource recovery solutions and the actions needed to facilitate implementation. The methodology comprised critical literature reviews and two case studies. Secondary data from literature and primary data (obtained through questionnaires) were collected and analysed. Megacities in developing countries are analysed in the papers, with the focus on the Macrometropolis of Sao Paulo, which is the most populous area in the Southern Hemisphere. The current situation shows a low implementation of resource recovery practices in the region, and local conditions affect the implementation of water reuse, nutrients and energy recovery. A framework consisting of eleven steps is proposed to support planning and decision-making on resource recovery from wastewater. This new tool was tested and can be applied by decision-makers in wastewater sector for better operation and management. Market, legislation, local economic development, and cooperation with stakeholders are relevant aspects covered in the analysis. There is a great potential to expand wastewater treatment integrated with nutrient and energy recovery strategies in developing countries. Potentials for phosphorus and energy recovery were estimated and some recovery scenarios are recommended. In conclusion, the findings can help planning and elaboration of resource recovery projects in wastewater treatment in urban areas and stimulate creation of public policies. The main research gaps identified in this thesis can guide further research and technological development in this field